THE LEGAL PROTECTION OF COMMUNITY RIGHTS IN AREA SPATIAL PLANNING OF MATARAM CITY BASE ON THE LOCAL REGULATION NUMBER 12 YEAR 2011 - Arba Arba (Fakultas Hukum Universitas Mataram, 2014)
This research aims to revile, analyze and comprehend the policy of the Spatial Plan in terms of the normative aspect, especially to analyze the legal protection of rights and community participation. This research will be conducted to analyze as normative the policies and strategies of spatial use patterns of Mataram City base on the Local Regulation of RTRW Number 12 Year 2011, and to analyze the legal protection and alignment to people’s rights as one of the stakeholders. This research is normative research, so the main approach method that used is normative approach, consist of the legislation approach (statute approach), conceptual approach), analytical approach, and historical approach. The results of research after analyzed as normative and qualitative, shows that conceptually the rights of individuals and communities have regulated and protected by the State Constitution, is the 1945 Constitution and the various legislations, particularly those regulation of Spatial Planning (Act Number 26 Year 2007, Government Regulation Number 15 Year 2010 and Government Regulation Number 68 Year 2010). In addition, base The Acts Number 12 Year 2011 on the Establishment of Legislation that every establishment of legislation should involve the community. As well as the Local Regulation of Spatial Plan Number 12 Year 2011 has regulated and protected clearly the rights and obligations of the community, but the community involvement in making RTRW is limited public consultation only. Though the forms of public participation base on the Acts and Government Regulations is not only a public consultation but the participation in preparing and planning the space regulation. Therefore, the Government of Mataram City in order to provide the legal protection of community rights as one of the stakeholders well, then after five years of enactment of Regulation, shall conduct a review, and public participation should be prioritized.Keyword : Policy, People Right, Special planing